2007
DOI: 10.1007/s11096-007-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical doctors’ perceptions and expectations of the role of hospital pharmacists in Sudan

Abstract: Respondents appeared receptive to most statements regarding expectations of pharmacists, suggesting that many elements of patient-centred pharmaceutical care could be introduced with the co-operation of physicians. A key to extending the role of pharmacists in Sudan teaching hospitals should involve making pharmacists more accessible to doctors and patients, ideally, supported by an organised program of continuing professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 19 publications
15
71
0
Order By: Relevance
“…Moreover, they are not opposed to having pharmacists involved in direct patient care [16]. Our finding is consistent with the finding of developed countries but some studies have shown in developing countries that healthcare providers considered the pharmacists as knowledge experts and they are comfortable with the pharmacists providing broad range of activities including patient care [17].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, they are not opposed to having pharmacists involved in direct patient care [16]. Our finding is consistent with the finding of developed countries but some studies have shown in developing countries that healthcare providers considered the pharmacists as knowledge experts and they are comfortable with the pharmacists providing broad range of activities including patient care [17].…”
Section: Discussionsupporting
confidence: 89%
“…This perception is mentioned by our informants and is consistent with Pakistani study conducted in 2009 [10], which reported that 47.2 % of the doctors strongly agreed to be assisted by the pharmacist in designing drug therapy treatment plans for the patients. Less than half of the respondents think that the pharmacists interact directly with the patients, this finding is in line with observation in different countries [17]. Moreover, on the other hand, it is also important that the pharmacists should better understand what the doctors expect from them and their perceptions to involve the pharmacists for the betterment of patient care.…”
Section: Discussionsupporting
confidence: 76%
“…The questionnaire used in this investigation was adapted with minor modifications from previously published studies [12][13][14][15]. The questionnaire was composed of four sections: Section 1(A) requested demographic information such as age, gender, place of work, current position and area of specialization, qualification year, and country of graduation.…”
Section: Subject and Designmentioning
confidence: 99%
“…The results varied from physicians being comfortable with pharmacists providing a broad range of services [12,13] to being uncomfortable even in the case of suggestions for minor illnesses [14,15]. The aim of this study was to evaluate physicians' perceptions expectations and experiences with pharmacists' professional services in Iraqi government hospitals.…”
Section: Introductionmentioning
confidence: 99%